Functional outcome of pannexin-deficient mice after cerebral ischemia - Bargiotas, Panagiotis; Krenz, Antje; Monyer, Hannah; Schwaninger, Markus (Channels, 2012)
Pannexin (Px, Panx) channels have been implicated in several physiological and pathological processes. We recently studied the potential contribution of pannexins in ischemic brain damage using Px1-/- Px2-/- mice and provided evidence that (1) the release of IL-1β and hemichannel function in astrocytes are, in contrast to published data, not affected by the absence of Px1 and Px2, (2) channel function in neurons lacking Px1 and Px2 is impaired and (3) Px1-/- Px2-/- mice had a better functional outcome and smaller infarcts than wild-type mice when subjected to ischemic stroke. Here, we further investigate the neurological outcome of wild-type and pannexin double-knockout mice 48 h after permanent occlusion of the distal middle cerebral artery (MCAO). Pannexin double-knockout mice (Px1-/- Px2-/-) were less impaired in parameters such as exploration, anxiety, sensorimotor function and behavioral symmetry.
Published online: 30 Oct 2012
Gesehen am 14.09.2018